Analisis Kesulitan Belajar Siswa Materi Bioteknologi SMA Negeri Se- Kabupaten Rokan Hilir - Zulpadly, Zulpadly; Harahap, Fauziyah; Edi, Syahmi (Jurnal Pendidikan Biologi, 2016)
This study aims to determine students learning difficulties in analyzing the material Biotechnology in view of the indicator. This research is descriptive quantitative study population of SMA as Rokan downstream terdir from SMAN 11 with a sample of as many as 644 people overall. The sampling technique used random sampling techniques. The data collection technique is a multiple-choice test instrument, for trouble indicator boteknologi materials, the data is processed by using a percentage. Judging from the indicators difficulties, learning difficulties on indicators derived their understanding of basic principles of biotechnology and 49.90%, explain the science related to biotechnology 46.44%, explaining the differences of traditional and modern biotechnology 52.23%, 67,44% Â Explaining the process of genetic engineering %, explaining 63.44% tissue culture process, explain the process of gene recombinant 63.07%, 48,60% Â describes an example of genetic engineering, explained the impact of the use of biotechnology 48.06%, describes the impact of using genetically engineered 63,17%.